Analyzing the Effectiveness of ChatGPT to Improve Student Writing Proficiency in Recount Texts - khairunniswa; Sholihatul Hamidah Daulay (Institut Agama Islam Negeri Palopo, 2024)
This research investigates the effectiveness of integrating ChatGPT, an AI language model, in enhancing students' proficiency in writing recount texts. By analyzing the impact of ChatGPT on students' writing skills, the study aims to evaluate the quality, coherence, and language proficiency of student-written outputs before and after incorporating the tool. Additionally, it seeks to identify and propose strategies to overcome potential barriers to maximize ChatGPT's impact on students' ability to write recount texts. The study's findings hold theoretical significance in advancing knowledge on AI integration in language education and practical implications for researchers, students, and teachers alike, offering insights into the potential benefits of AI technologies in writing instruction.